Evaluasi Keberlanjutan Perikanan Tuna Sirip Kuning Di WPP-715, Maluku Utara: Pendekatan Pemodelan Bioekonomi - Kadir, Irwan Abdul; Rumagia, Faizal; Wulandari, Tri L. (Amanisal: Jurnal Teknologi dan Manajemen Perikanan Tangkap, 2025)
Yellowfin tuna is a valuable fishery resource in WPP-715, North Maluku, Indonesia, contributing significantly to both local economies and global tuna markets. However, overfishing and unsustainable practices threaten the long-term viability of this resource. This study aims to assess the current level of fish exploitation and analyze appropriate management strategies for yellowfin tuna fisheries in WPP-715. The Cost-Yield-Profit (CYP) model was used to evaluate optimal fisheries from both input and output perspectives. The result in this study shows that bioeconomic assessment shows that under (Maximum Sustainable Yield) MSY conditions, biomass reached 2,617,152 kg with a catch of 577,292 kg and 20,353 fishing trips. Under (Maximum Economic Yield) MEY conditions, biomass was higher at 3,226,476.00 kg with a catch of 546,000 kg and 15,614 fishing trips, yielding a maximum economic benefit of Rp 18,008,031,386. Bioeconomic analysis revealed that the current state of the fishery is overfished, exceeding both MSY and MEY levels. This study underscores the urgent need for sustainable management strategies to prevent further stock depletion and economic losses.